Effect of residual air bubbles on diesel spray structure at the start of injection. (1st April 2019) - Ghiji, M.; Goldsworthy, L.; Garaniya, V.; Brandner, P.A.; Hield, P.; Novozhilov, V.; Moinuddin, K.; Joseph, P.
Highlights: Effects of residual air bubbles on diesel spray dynamics are investigated. Structure of the jet at the early stage of injection is analyzed. Experimental and numerical approaches are employed to provide further insights. The transparency of the liquid jet at the start of injection is discussed. Abstract: Experimental and numerical analyses of the effect of residual air bubbles in a single-hole high-pressure diesel injector nozzle are presented. Detailed information on spray structures and dynamics near nozzle exit at the Start of Injection (SOI) is described. Experimental measurements are performed using a laser-based backlit imaging technique through a long distance microscope by injecting diesel fuel into a constant volume high-pressure spray chamber. Numerical investigation of, in and near-nozzle fluid dynamics is conducted in an Eulerian framework using a Volume of Fluid (VOF) interface capturing technique integrated with Large Eddy Simulation (LES) turbulence modelling. The present flow setup includes residual air bubbles remaining from a previous injection event, in-nozzle turbulence with no-slip wall conditions. Experimental images show a toroidal starting vortex near the nozzle exit suggesting a partially filled nozzle; transparency in the emerging jet demonstrates the presence of air trapped inside the nozzle liquid from the previous injection event. The numerical model provides insight into the influence of residual air bubbles on the spray morphology and dynamics of the emerging jet at the SOI. A mathematical code is developed to replicate the backlit imaging approach with the numerical results. The virtual images demonstrate a transparent liquid jet emerging into the pressurized chamber gas showing improved agreement with experimental images. The inclusion of air bubbles in the nozzle liquid prior to injection in the numerical model also yields improved agreement in the penetration velocity profile of the jet. These results explain how inclusion of residual air bubbles inside the nozzle liquid affects the physics of the penetrating jet at the SOI. The air bubbles inclusion also provides an explanation for the transparency of the emerging jet, rough interfacial surfaces, and enhanced necking behind the jet tip captured at the SOI.